2017
DOI: 10.1007/s11748-017-0789-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and outcomes of vasoplegia after cardiac surgery

Abstract: Vasoplegic syndrome is still a frequently occurring adverse event following cardiac surgery. In high risk patients for vasoplegia, it may be sensible to proceed with preoperative volume loading (instead of diuresis), initiation of low dose vasopressin therapy if needed, and attempting to up titrate beta-blocker therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 25 publications
3
53
1
Order By: Relevance
“…Elderly patients often present with multiples comorbidities that may enhance the IR 20. Despite the absence of association in our study, the p-value is almost significant and it probably requires a larger study to demonstrate this relationship.…”
Section: Discussioncontrasting
confidence: 65%
“…Elderly patients often present with multiples comorbidities that may enhance the IR 20. Despite the absence of association in our study, the p-value is almost significant and it probably requires a larger study to demonstrate this relationship.…”
Section: Discussioncontrasting
confidence: 65%
“…Although there is an overall agreement regarding the effect of specific risk factors for VS, other factors are more controversial. In recent literature, chronic hemodialysis (HD)-dependent renal failure has been suggested to be a risk factor for VS because of its chronic inflammatory status [10,11]. Repeated dialysis treatments in patients with chronic renal failure (CRF) are considered to promote an inflammatory response [12], although the duration of HD has not yet been examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Commonly used treatments include fluid resuscitation, vasopressors, and methylene blue. One study 6 suggested that diuretics increase the risk of vasoplegia because diuretics-induced hyponatremia can blunt the arginine vasopressin response.…”
mentioning
confidence: 99%
“…The authors reported that the use of continuous-flow ventricular assist device support was associated with a higher incidence of vasoplegia and that no other variables were related to the incidence of vasoplegia. Tsiouris et al 6 investigated the risk factors, vulnerable patient populations, and the cost of postoperative vasoplegia. They demonstrated that vasoplegia is associated with worse survival postoperatively and is commonly seen in patients with heart failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation